2022
DOI: 10.1007/s12026-022-09350-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory activity of fluoxetine in macrophages via regulation of the PI3K and P38 signaling pathways

Abstract: Fluoxetine is an antidepressant drug that is heavily preferred in the cure of depression, which is from the selective serotonin reuptake inhibitor (SSRI) group. There are many reports on the effect of fluoxetine on the immune system, and its effect on the macrophage cells has never been looked at before. We aimed to demonstrate the cytokine production potential of fluoxetine antidepressant, which is widely used in the clinic, in the J774.2 cell line and its effect on PI3K and P38 pathways. The use of fluoxetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…Thus, our data indicated that, at Dysregulation of cutaneous PI3K signalling may lead to severe pathological conditions characterized by uncontrolled cutaneous proliferation and inflammation, 59,86 and FX was already shown to interfere with this pathway. [38][39][40][41] Thus, our findings argued that, at least when applied at 14 μM, FX may exert its beneficial actions by directly or indirectly inhibiting the PI3K pathway. In order to challenge this hypothesis, we repeated our experiments by using the aforementioned PI3K inhibitor (GDC0941; 370 nM).…”
Section: Fx Exerts Its Anti-inflammatory Actions Most Likely Via Inte...mentioning
confidence: 58%
See 4 more Smart Citations
“…Thus, our data indicated that, at Dysregulation of cutaneous PI3K signalling may lead to severe pathological conditions characterized by uncontrolled cutaneous proliferation and inflammation, 59,86 and FX was already shown to interfere with this pathway. [38][39][40][41] Thus, our findings argued that, at least when applied at 14 μM, FX may exert its beneficial actions by directly or indirectly inhibiting the PI3K pathway. In order to challenge this hypothesis, we repeated our experiments by using the aforementioned PI3K inhibitor (GDC0941; 370 nM).…”
Section: Fx Exerts Its Anti-inflammatory Actions Most Likely Via Inte...mentioning
confidence: 58%
“…~0.4–2 μM) 76,77 found in FX‐treated patients. This, together with the aforementioned reports, 34,36–41 argued that the effects of FX may be mediated via the modulation of unexpected cellular targets. Having excluded three potential anti‐inflammatory mechanisms (i.e.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations